Characterization and Exploitation of CRISPR Loci in Bifidobacterium longum - Hidalgo-Cantabrana, Claudio; Crawley, Alexandra B.; Sanchez, Borja; Barrangou, Rodolphe (Frontiers in Microbiology, 2017)
Diverse CRISPR-Cas systems provide adaptive immunity in many bacteria and most archaea, via a DNA-encoded, RNA-mediated, nucleic-acid targeting mechanism. Over time, CRISPR loci expand via iterative uptake of invasive DNA sequences into the CRISPR array during the adaptation process. These genetic vaccination cards thus provide insights into the exposure of strains to phages and plasmids in space and time, revealing the historical predatory exposure of a strain. These genetic loci thus constitute a unique basis for genotyping of strains, with potential of resolution at the strain-level. Here, we investigate the occurrence and diversity of CRISPR-Cas systems in the genomes of various Bifidobacterium longum strains across three sub-species. Specifically, we analysed the genomic content of 66 genomes belonging to B. longum subsp. longum, B. longum subsp. infantis and B. longum subsp. suis, and identified 25 strains that carry 29 total CRISPR-Cas systems. We identify various Type I and Type II CRISPR-Cas systems that are widespread in this species, notably I-C, I-E and II-C. Noteworthy, Type I-C systems showed extended CRISPR arrays, with extensive spacer diversity. We show how these hypervariable loci can be used to gain insights into strain origin, evolution and phylogeny, and can provide discriminatory sequences to distinguish even clonal isolates. By investigating CRISPR spacer sequences, we reveal their origin and implicate phages and prophages as drivers of CRISPR immunity expansion in this species, with redundant targeting of select prophages. Analysis of CRISPR spacer origin also revealed novel PAM sequences. Our results suggest that CRISPR-Cas immune systems are instrumental in mounting diversified viral resistance in Bifidobacterium longum, and show that these sequences are useful for typing across three subspecies.